2015
DOI: 10.1016/j.ijgo.2015.04.032
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of mental health morbidity and its associated factors among women attending a prenatal clinic in Tanzania

Abstract: Many pregnant women had symptoms of mental health disorders. Screening of mental health disorders during prenatal care and training of healthcare providers are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 21 publications
2
28
0
4
Order By: Relevance
“…11 Consequently, the gestational period is affected by such prevalences, with all the body and lifestyle changes, becoming a stressor for women's experience 7 This had been confirmed in a previous study with 1,180 pregnant women, as it revealed that symptoms of anxiety (76.7%) and depression (78.2%) are more prevalent in young women aged between 17 and 29 years who are married. 12 In particular, regarding depression symptoms, being single was associated with a higher risk of development of depression during the gestational period, 6 corroborating the present study in which women living without a partner were more likely to have CMD.…”
Section: Discussionsupporting
confidence: 85%
“…11 Consequently, the gestational period is affected by such prevalences, with all the body and lifestyle changes, becoming a stressor for women's experience 7 This had been confirmed in a previous study with 1,180 pregnant women, as it revealed that symptoms of anxiety (76.7%) and depression (78.2%) are more prevalent in young women aged between 17 and 29 years who are married. 12 In particular, regarding depression symptoms, being single was associated with a higher risk of development of depression during the gestational period, 6 corroborating the present study in which women living without a partner were more likely to have CMD.…”
Section: Discussionsupporting
confidence: 85%
“…Reported prevalence of depression ranged from 6.9% to 78.2% (Mahenge et al 2015;Raja Lexshimi et al 2003;Rwakarema et al 2015). This current study reported 12.5% of women had probable depression.…”
Section: Discussionsupporting
confidence: 43%
“…These factors included women's age, parity, educational level, loss of a planned pregnancy, history of subfertility, conception via artificial reproductive technique (ART), prior miscarriage or induced abortion, low socioeconomical income and presence of marital conflict (Mahenge et al 2015;Fergusson et al 2013;Chalana and Sachdeva 2012;McCarthy et al 2015;Cheung et al 2013). To date, the results have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were predominantly conducted in the USA (k = 18, 30.5%), followed by Sweden (k = 5, 8.5%) and the Netherlands (k = 4, 6.7%). Samples were all female and homogenous in terms of ethnicity with predominantly white women, with five exceptions of studies conducted in African countries (Adewuya et al, 2006a;Adewuya et al, 2006b;Busari, 2010;Mahenge et al, 2015;Spies et al, 2009). …”
Section: 1study Characteristicsmentioning
confidence: 99%